Woman Resistance toward Domestic Roles in “Little Women” Novel by Louisa May Alcott: Feminist Approach - Lavinia Rosemary; Tomi Arianto (Humanitatis : Journal of Language and Literature, 2023)
Women’s resistance toward domestic roles is viewed from the main characters in the novel “Little Women”. This research aimed to see and analyze women's resistance toward domestic roles in the novel “Little Women” by Louisa May Alcott using Tiffany K Wayne theory of triple roles and feminism approach. To find out what kind of roles of women shown by the main characters in the novel “Little Women” based on triple roles theory by Tiffany K Wayne.To find out how women's resistance toward domestic roles can be seen from the characters in the novel "Little Women" by Louisa May Alcott. Several forms of women's resistance to domestic roles as reflected in the actions taken by the main female characters in the novel Little Women, including: Women can freely express their gender, women deserve to be educated, and the last is women can choose to carry out any role in their life. This research is using Qualitative data analysis is a way for working with data, organizing it, and classifying it into manageable components. The result is women's resistance to domestic roles as reflected in the actions taken by the main female characters in the novel Little Women, including: Women can freely express their gender, women deserve to be educated, and the last is women can choose to carry out any role in their life.